THE PURCHASE OF COMPUTERIZED ADMINISTRATION SYSTEM DESIGN FACILITIES AND INFRASTRUCTURE RECOVERY OF OIL PALM PLANTATIONS AT PT. RAWIT INTERJASA - Dahana Dahana; Eko Hadiyanto, SSI, MMSI Eko Hadiyanto, SSI, MMSI (Jurnal Sistem Informasi, 2001)
An entity entered into the purchase because it requires a business entity of goods orservices to be purchased. So the purchase is to meet the demand for goods. The taskto make the purchase of this venom is used by a department, namely the purchasingdepartment headed by a manager and is assisted by a few employees. In general, thepurchasing department is in addition to making contact with the seller or partner,must also prepare the necessary documents.In order to prepare the documents, required a reliable system, within the meaning ofwords can be relied upon in terms of both time efficient process, and in terms ofsupporting a decision-making, in this case is the decision in the purchase of goodsfacilities and infrastructure maintenance coconut plantations oil palm PT. RawitInterjasa.